Students’ writing skill through Telecollaboration: in the context of WhatsApp and Facebook - Safiatur Rokhmah (Loquen, 2020)
This study focused on observing, identifying potential problems, modifying teaching practices, evaluating the results, reflecting and analyzing the teaching writing skills through telecollaboration. The participants of the research were the students of MA Al Jauharotun Naqiyyah Cibeber grade XII with the total number of 15 students. The students were selected based on the pre-observation writing result which was conducted at the beginning of new term. The selected participants were being taught writing through telecollaboration then observed their progress in learning English writing. The results of the study found that the use of ICT and digital media such as Facebook and WhatsApp application help students in making learning outside school hours. It also motivated students to use English.